Atorvastatin combined with ticagrelor prevent ischemia-reperfusion induced vascular endothelial dysfunction in healthy young males – A randomized, placebo-controlled, double-blinded study. (15th March 2018) - Weisshaar, Stefan; Litschauer, Brigitte; Kerbel, Tillmann; Wolzt, Michael
Abstract: Background: Atorvastatin and ticagrelor have been shown to prevent against tissue injury in animals. It is unclear if these beneficial effects are also detectable in humans. We studied the effect of high-dose atorvastatin combined with ticagrelor loading on endothelial dysfunction in a model of forearm vascular ischemia-reperfusion (IR) injury. Methods: 32 healthy subjects (n = 16 per group) were enrolled in this randomized, placebo-controlled, double-blinded trial. Forearm blood flow (FBF) measurements in response to increasing intra-arterial doses of the vasodilator acetylcholine (ACh; endothelium-dependent agonist) and glyceryltrinitrate (GTN; endothelium-independent) were performed before and after a cuff-induced 20 min forearm ischemia, respectively. FBF reactivity was assessed prior to any pharmacological intervention and after 14 days intake of 80 mg atorvastatin once daily or placebo, followed by an oral loading dose of 180 mg ticagrelor. In addition, lipoprotein parameters and platelet aggregation were evaluated. Results: Ticagrelor loading mitigated ischemia-induced endothelial dysfunction and in combination with repeated atorvastatin dosing the response to ACh during reperfusion was completely normalized (FBF AChAUC ratio post- vs. pre-ischemia: 0.81 [ticagrelor] vs. 1.04 [atorvastatin + ticagrelor]; P = 0.001). As expected, GTN-induced vasodilation was not affected by IR injury. Atorvastatin significantly reduced total and low density lipoprotein cholesterol concentrations, while high density lipoprotein cholesterol and triglyceride levels remained unchanged. Conclusion: Chronic atorvastatin treatment combined with ticagrelor loading prevents against endothelial dysfunction after acute forearm ischemia. Ticagrelor alone mitigated the impaired endothelium-dependent FBF response as compared to no pharmacological intervention. Clinical trial registration: URL:https://clinicaltrials.gov . Unique identifier:NCT02910778 . Highlights: The first trial in humans investigating ischemia-reperfusion induced endothelial dysfunction during combined atorvastatin and ticagrelor intake. Atorvastatin with ticagrelor loading exerted a greater salutary effect after ischemia than ticagrelor alone. Combined atorvastatin and ticagrelor treatment completely prevented ischemia-reperfusion induced endothelial dysfunction.